1974
DOI: 10.2134/agronj1974.00021962006600010015x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ammonium and Nitrate Forms of Fertilizer‐N and their Time of Application on Utilization of N by Wheat1

Abstract: A hypothesis was tested: that NH4+‐N applied early and NO3−‐N applied later would be a beneficial cultural practice for wheat production. It is generally agreed that cereals prefer NH4+‐N during early growth. One growth chamber and three field experiments were conducted with wheat (Triticum aestivum var. Manitou) using ammonium (NH4+‐N) and nitrate (NO3−‐N) sources of fertilizer‐N applied either at sowing or as the heads emerged or at both times. A nitrification inhibitor was used with ammonium sulphate to sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
12
0

Year Published

1978
1978
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 4 publications
4
12
0
Order By: Relevance
“…In treatments containing both NH 4 + and N0 3 , uptake of NH 4 * was higher than N0 3 " in the first 2 wk after transfer to the solution, similar to the results of Spratt (12) working with wheat ( Fig. 1).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In treatments containing both NH 4 + and N0 3 , uptake of NH 4 * was higher than N0 3 " in the first 2 wk after transfer to the solution, similar to the results of Spratt (12) working with wheat ( Fig. 1).…”
Section: Resultssupporting
confidence: 83%
“…was observed to drop 80-95% at mid-pod fill, a time when a heavy demand is placed on the plant for energy by the developing seeds (10). Some plants show a preference for a particular form of N. It is generally agreed that cereals prefer NH 4 + during early growth (12). Mills and McElhannon (11) found that corn also preferred NH 4 * after tasseling.…”
mentioning
confidence: 99%
“…early leaves and stems) than does nitrate nitrogen (Spratt & Gasser, 1970). Nitrate applied to wheat as the heads emerge (boot stage) increases the protein in the grain more than does applied ammonium (Spratt, 1974). Thus the effects of ammonium and nitrate on wheat seem to be quite different from those on the dicotyledonous flowering plants mentioned earlier.…”
Section: (B) Organic Acidsmentioning
confidence: 84%
“…Previously Vaughan et al (1990a) concluded that the observed differences between critical N levels could be due to the differences in the growing conditions in varying geographical regions and/or wheat classes. The study of Spratt (1974) indicated that critical N0 3 -N concentration of 300 ppm in dry-matter (DM) of above-ground parts of plant at anthesis was required for optimum grain protein concentration in grains. Peltonen (1992), in turn, showed that differences in R 2 in tissue N content between different plant parts at anthesis were insufficient to justify any particular choice of plant parts for sampling in the field.…”
Section: Relationship Between Tissue Nitrogen Concentration and Crop mentioning
confidence: 99%